ANALISIS PELATIHAN INOVASI DALAM MENGEMBANGKAN USAHA PRODUK PISANG PADA PELAKU UMKM DI DESA DHARMA BHAKTI - Ansela Sella; Nuraini Astriati; Syamsuri Syamsuri; Junaidi H Matsum; Husni Syahrudin (Jurnal Pendidikan Ekonomi (JURKAMI), 2026)
MSMEs play a strategic role in strengthening rural economies; however, limited product innovation remains a key challenge. This study analyzes innovation training in banana processing among MSME actors in Dharma Bhakti Village, focusing on capacity building, product innovation, and supporting and inhibiting factors. The research subjects are banana-processing MSMEs affiliated with the PKK, while the research object includes innovation training and banana-based business development. A descriptive qualitative approach was employed through observation, interviews, and documentation. The findings indicate that innovation training enhances knowledge, skills, and entrepreneurial motivation, reflected in product diversification, improved quality, better packaging, and simple marketing strategies. Supporting factors include village government support, the active role of PKK, and adequate facilities, while constraints involve limited time, high costs, and restricted market access. The study highlights the need for continuous training and stronger support for capital and marketing, with limitations related to the small number of participants and the focus on a single village.